Evaluation of Intracranial Arteriovenous Malformations With Four-Dimensional Arterial-Spin Labeling–Based 3-T Magnetic Resonance Angiography. Issue 2 (March 2016) - Iryo, Yasuhiko; Hirai, Toshinori; Nakamura, Masanobu; Kawano, Takayuki; Kaku, Yasuyuki; Ohmori, Yuki; Kai, Yutaka; Azuma, Minako; Nishimura, Shinichiro; Shigematsu, Yoshinori; Kitajima, Mika; Yamashita, Yasuyuki
Abstract : Objective: We aimed to assess the usefulness of 3-T 4-dimensional (4D) arterial spin-labeling (ASL)–based magnetic resonance angiography (MRA) with color-coded time-of-arrival (TOA) maps for the evaluation of cerebral arteriovenous malformations (AVMs). Methods: Our study included 6 patients with cerebral AVMs. They underwent 4D-ASL MRA at 3T and digital subtraction angiography. A pseudocontinuous arterial spin labeling protocol with look-locker sampling was used for spin labeling. Two independent readers reviewed the 4D-ASL MRA images with color-coded TOA maps for the nidus size, arterial feeders, and venous drainage. Two other readers consensually reviewed the digital subtraction angiography images. Results: The cerebral AVMs were demonstrated on all 4D-ASL MRA images. In 5 high-flow AVMs, the color-coded TOA maps were especially useful for identifying the feeder/drainer. Intermodality agreement was excellent for the nidus size (κ = 1.0), very good for arterial feeders (κ = 0.88), and good for venous drainage (κ = 0.80). Conclusions: The 4D-ASL 3-T MRA with color-coded TOA maps is useful for assessing the gross angiographic characteristics of intracranial AVMs.